Analisis Forecasting Volume Kontainer di Cikarang Dry Port Pada Tahun 2023 Menggunakan Metode Exponential Smoothing Brown, Winter dan Quadratik - Nafisah, Durotun; Farida, Siti Ning (Universitas Labuhanbatu, 2024)
To regulate business activities that take place at Cikarang Dry Port, there is a process to predict what will happen to the company's operations in the future. The process of predicting things like this is called forecasting. This research aims to determine an effective forecasting method for the Cikarang Dry Port using exponential smoothing forecasting methods such as the Brown method, Winter method and Quadratic method. After the analysis is carried out, the smallest MAD (Mean Absolute Error) will be determined. This research uses a qualitative descriptive method to create a forecasting picture at the Cikarang Dry Port using secondary data obtained through container volume reports at the Cikarang Dry Port over the last year. The research results show that the Exponential Smoothing method from Winter is more suitable for estimating the volume of Cikarang Dry Port containers with forecasting results of 9750 TEUs with the smallest error, namely 1537.